2018
DOI: 10.1016/j.mtener.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

2D Hydrogenated graphene-like borophene as a high capacity anode material for improved Li/Na ion batteries: A first principles study

Abstract: Fast-growing electronics industry and future energy storage needs have encouraged the design of rechargeable batteries with higher storage capacities, and longer life times. In this regard, two-dimensional (2D) materials, specifically boron and carbon nanosheets, have garnered enthusiasm due to their fascinating electronic, optical, mechanical and chemical properties. Recently, a hydrogen boride (HB) nanosheet was successfully fabricated showing remarkable stability and superior physical properties. Motivated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 76 publications
6
53
1
Order By: Relevance
“…The calculated average voltages of Li 2 x Si 2 H 2 and Na 2 x Si 2 H 2 are 0.42 and 0.64 V, respectively. These voltages lie below the previous attempts made for Li x PC (0.76 V), Na x PC (0.74 V), Li x B 2 C (0.57 V), Na x B 2 C (0.43 V), Na x C (graphdiyne; 0.56 V), and Li x Br (0.65 V) [34b,36] . Thus, the obtained voltages provide an efficient approach towards high‐performance anodes of LIBs and NIBs.…”
Section: Resultscontrasting
confidence: 57%
“…The calculated average voltages of Li 2 x Si 2 H 2 and Na 2 x Si 2 H 2 are 0.42 and 0.64 V, respectively. These voltages lie below the previous attempts made for Li x PC (0.76 V), Na x PC (0.74 V), Li x B 2 C (0.57 V), Na x B 2 C (0.43 V), Na x C (graphdiyne; 0.56 V), and Li x Br (0.65 V) [34b,36] . Thus, the obtained voltages provide an efficient approach towards high‐performance anodes of LIBs and NIBs.…”
Section: Resultscontrasting
confidence: 57%
“…In these years, computational studies suggested that some 2D hydrogen borides (HBs) should exhibit unique electronic properties (as summarized in Figures S1-S7). [11][12][13][14][15] Because of the electronic configuration of boron, a variety of 2D boron hydride structures are energetically favorable, as corroborated computationally (cf. Table S1).…”
Section: Introductionmentioning
confidence: 78%
“…It is worth noting that N-graphdiyne monolayers outperform other anode candidates for LIB including commercial anode materials; such as graphite and TiO2 with capacities of 372 mAh/g and 200 mAh/g; respectively, [63][64][65] Figure 4 shows the electronic density of states (DOS) of different pristine N-graphdiyne nanosheets, and the ones embedding Li/Na adatoms. Although, at the beginning the pristine C18N6, C24N4, and C36N6 crystals exhibit semiconducting behavior (involving the energy gaps of 2.20, 0.50 and 1.10 eV, respectively), they all develop the metallic band gap after the insertion of one Li/Na foreign atom.…”
Section: Resultsmentioning
confidence: 99%